1990
DOI: 10.1111/j.1365-3059.1990.tb02536.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the abaxial leaf surface waxes of Lolium spp. in resistance to Erysiphe graminis

Abstract: Field and glasshouse observations of Lolium spp. grasses indicated that the lower, abaxial, leaf surface was rarely infected by powdery mildew (Erysiphe graminis) even when the upper, adaxial, surface was densely colonized. Experiments showed that conidia of two strains of E. graminis, one from Lolium and one from Avena, germinated equally well on both surfaces of Lolium and Avena leaves, but that the subsequent growth and development of germlings was impaired on the lower surface of Lolium leaves, so that mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Our results showed that irg1/palm1 mutants were completely devoid of wax crystals on the abaxial leaf surface and suggested a possible role for signals at the cuticle interface, especially the components of the leaf wax in promotion or inhibition of rust preinfection structure differentiation on the abaxial leaf surface of the irg1 mutants (Figures 1 and 2). Consistent with our results, two other previous studies have shown normal development of fungal preinfection structures on the adaxial surface and short germ tubes with few appressoria on abaxial leaf surfaces during host-specific pathogenic interactions involving wild-type pea (Pisum sativum)-E. pisi and wild-type ryegrass (Lolium spp)-Erysiphe graminis interactions (Carver et al, 1990;Gniwotta et al, 2005). Variations in wax crystal composition between adaxial and abaxial leaf surfaces were implicated in pea-E. pisi interactions (Gniwotta et al, 2005).…”
Section: Discussionsupporting
confidence: 80%
“…Our results showed that irg1/palm1 mutants were completely devoid of wax crystals on the abaxial leaf surface and suggested a possible role for signals at the cuticle interface, especially the components of the leaf wax in promotion or inhibition of rust preinfection structure differentiation on the abaxial leaf surface of the irg1 mutants (Figures 1 and 2). Consistent with our results, two other previous studies have shown normal development of fungal preinfection structures on the adaxial surface and short germ tubes with few appressoria on abaxial leaf surfaces during host-specific pathogenic interactions involving wild-type pea (Pisum sativum)-E. pisi and wild-type ryegrass (Lolium spp)-Erysiphe graminis interactions (Carver et al, 1990;Gniwotta et al, 2005). Variations in wax crystal composition between adaxial and abaxial leaf surfaces were implicated in pea-E. pisi interactions (Gniwotta et al, 2005).…”
Section: Discussionsupporting
confidence: 80%
“…There is however evidence of non-race-specific resistance to powdery mildew (Erysiphe graminis) . The epicuticular wax on the undersurface of ryegrass leaves, which gives the genus its distinctive shiny appearance, confers partial resistance to powdery mildew since most conidia fail to germinate on this wax (Carver et al ., 1991) .…”
Section: Main Breeding Objectivesmentioning
confidence: 99%
“…This is not confined to rust fungi since Carver et al (1990) also found that the sheet-like waxes on the abaxial surface of L. temulentum prevented normal germination of conidia of Erysiphe graminis. On the other hand, the ability of leaves of Lolium species to fold in response to changing environmental conditions and the undulating topography of the upper surface might create a favourable micro-climate for urediospore germination on the adaxial surface.…”
Section: Discussionmentioning
confidence: 97%
“…The cereal hosts of rusts have crystalline waxes on both leaf surfaces (e.g. Carver et al, 1990) and crown rust (P. coronata f.sp. avenae) can infect through stomata on both these surfaces (Kochman & Brown, 1976;Roderick & Thomas, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation